The bioelectrical properties of bone tissue - Heng, Boon Chin *; Bai, Yunyang; Li, Xiaochan; Meng, Yanze; Lu, Yanhui; Zhang, Xuehui; Deng, Xuliang (Wiley Open Access, 2023)
Understanding the bioelectrical properties of bone tissue is key to developing new treatment strategies for bone diseases and injuries, as well as improving the design and fabrication of scaffold implants for bone tissue engineering. The bioelectrical properties of bone tissue can be attributed to the interaction of its various cell lineages (osteocyte, osteoblast and osteoclast) with the surrounding extracellular matrix, in the presence of various biomechanical stimuli arising from routine physical activities; and is best described as a combination and overlap of dielectric, piezoelectric, pyroelectric and ferroelectric properties, together with streaming potential and electro-osmosis. There is close interdependence and interaction of the various electroactive and electrosensitive components of bone tissue, including cell membrane potential, voltage-gated ion channels, intracellular signaling pathways, and cell surface receptors, together with various matrix components such as collagen, hydroxyapatite, proteoglycans and glycosaminoglycans. It is the remarkably complex web of interactive cross-talk between the organic and non-organic components of bone that define its electrophysiological properties, which in turn exerts a profound influence on its metabolism, homeostasis and regeneration in health and disease. This has spurred increasing interest in application of electroactive scaffolds in bone tissue engineering, to recapitulate the natural electrophysiological microenvironment of healthy bone tissue to facilitate bone defect repair.